IMPACT OF GENDER ON STUDENTS’ INTEREST AND ACHIEVEMENT IN BIOLOGY IN TECHNOLOGY ENHANCED LEARNING ENVIRONMENT - Eya, Patrick Eke; Odunukwe, Charity Ngozi; Eya, Gloria Ngboyibo; Nwanya, Darlington Uzoma (The Gender Truth Journal, 2024)
The study examined the impact of gender on students' interest and achievement in biology in a technology-enhanced learning environment (TELE). Two research questions and two null hypotheses guided the study. The study employed a quasi- experimental research design. The population of the study consisted of 191 first- year students (43 males, 148 females) of Biology Education in five federal universities in Southeast Nigeria. The sample consisted of 172 first-year students (38 males, 134 females) from three federal universities in the population of the study. Intact classes were used for the study. The treatment and test instruments were an Instructional Computer Animation Package, a Biology Achievement Test (BAT), and a Biology Interest Scale (BIS). The instruments were validated and trial- tested. Reliability coefficients of 0.8 and 0.70 were established for BAT and BIS respectively. Research questions were answered using mean and standard deviation while Analysis of Covariance (ANCOVA) was used to test the null hypotheses at a 0.05 level of significance. The result revealed that TELE had a significant positive effect on both male and female students' interest and achievement in biology. However, male students had statistically higher interest than female students while female students had higher achievement mean scores than male students. The difference was not statistically significant. Based on the findings, it was recommended that TELE be adopted by lecturers in teaching abstract and complex processes in biology. The researchers recommended that further research work be carried out on the effectiveness of TELE on undergraduate students' interest and achievement in other complex science processes.